From Housewife to Entrepreneur through Homemade Accessories: Challenges and Opportunities in Pandemic - Riezky Maya Probosari; Budi Utami; Ashadi Ashadi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The Covid-19 pandemic has an impact on increasing activity in the home. Changes in communication patterns and routines provide many new perspectives, especially for homemakers. The Family Welfare Program Association in the Karanganyar area, Central Java, Indonesia, mostly non-productive housewives, complained about the decline in family income due to changing activities. The increasing needs of the family have made this group want to develop their potential and increase their family income through training in making various crafts, in the form of patchwork-based accessories. This activity is carried out through community development practices, consisting of forming a team, formulating goals, analyzing needs, determining priority problem solutions, implementing, mentoring, and reviewing and evaluating.The activity results are in the form of various women's accessories and are marketed online through various kinds of social media. In the short term, this activity is intended so that all partners experience an increase in welfare. In the long term, it is hoped that this activity can initiate home industry groups in the surrounding area and further enhance Karanganyar's identity as a producer of accessories from used materials with aesthetics to improve skills in entrepreneurial accessories management and succeed in marketing